1998
DOI: 10.1161/01.str.29.9.1952
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment With an Adenosine Kinase Inhibitor, GP683, Attenuates Infarct Size in Rats With Temporary Middle Cerebral Artery Occlusion

Abstract: Background and Purpose-Brain ischemia is associated with a marked increase in extracellular adenosine levels. This results in activation of cell surface adenosine receptors and some degree of neuroprotection. Adenosine kinase is a key enzyme controlling adenosine metabolism. Inhibition of this enzyme enhances the levels of endogenous brain adenosine already elevated as a result of the ischemic episode. We studied a novel adenosine kinase inhibitor (AKI), GP683, in a rat focal ischemia model. Methods-Four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 58 publications
3
42
1
Order By: Relevance
“…37 Many other image analysis softwares are used for measuring the infarct areas in different experiments. 3,12,14 In our experiment, two hours of MCAO in control animals resulted in the infarct volume of 217.3 ± 79.5 mm 3 (corrected infarct volume), which is similar with the infarct volume of 210.39 ± 31.25 mm 3 (corrected infarct volume) after two hours of MCAO in another report. 36 The isoflurane-induced rapid tolerance to cerebral ischemia might be used to manage patients undergoing surgical procedures in which cerebral ischemia may occur.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…37 Many other image analysis softwares are used for measuring the infarct areas in different experiments. 3,12,14 In our experiment, two hours of MCAO in control animals resulted in the infarct volume of 217.3 ± 79.5 mm 3 (corrected infarct volume), which is similar with the infarct volume of 210.39 ± 31.25 mm 3 (corrected infarct volume) after two hours of MCAO in another report. 36 The isoflurane-induced rapid tolerance to cerebral ischemia might be used to manage patients undergoing surgical procedures in which cerebral ischemia may occur.…”
Section: Discussionsupporting
confidence: 90%
“…35 The ischemic model used in our experiments is widely accepted. 3,9,12,36 In the present study, the infarct areas were measured by using Adobe Photoshop, the method was also used for measuring the infarct areas in the heart. 37 Many other image analysis softwares are used for measuring the infarct areas in different experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that acupuncture preconditioning can exert favorable protective effects on hypoxia and ischemia in the heart, brain, gastrointestinal tract, and spinal cord, and it has been suggested that preconditioning induces a protective effect via generation of a trigger factor [31]. Our present results showed a greater effect in the Jiaji electroacupuncture preconditioning group than in the postinjury electroacupuncture treatment group.…”
Section: Discussionsupporting
confidence: 45%
“…Reperfusion has been shown to enhance injury due to production of reactive oxygen species and increased edema (Kuroiwa et al, 1988;Lipton and Rosenberg, 1994) but also allows for restoration of metabolic activity to the compromised areas (Hallenbeck and Dutka, 1990;Halsey et al, 1991). Critically, this model is well established and been shown to be highly sensitive to pharmacological intervention with neuroprotective drugs as a means to reduce the resulting brain infarction (Britton et al, 1997;Clemens and Panetta, 1994;Kawasaki-Yatsugi et al, 1998;Tatlisumak et al, 1998;Tortella et al, 1999;. Previous studies with MLN519 have reported neuroprotection in this same model of MCAO with a dose of 0.1 mg/kg delivered 4 hours after MCAO , as well as in combination with tissue plasminogen activator in a model of embolic stroke in rats (Zhang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%